Mektup, Hatıra ve Benzeri Yazıların Kişilik Hakkı Kapsamında Korunması - (:unkn) unknown (My University, 2019)
5846 sayılı Fikir ve Sanat Eserleri Kanunu’nun 85. maddesi mektup, hatıra ve benzeri yazılarınyayımlanmasına ilişkin birtakım kurallar getirmektedir. Böylece yazarın veya muhatabın gizli ve özelhayatlarına ilişkin bilgilerin korunması amaçlanmaktadır. Bu tür bilgileri içeren yazıların bir hukukauygunluk nedeni olmaksızın yayımlanması kişilik hakkının ihlaline neden olur. Dolayısıyla hükmünihlali halinde gizli veya özel hayat alanlarına saldırıda bulunulan kişiler kişilik hakkının ihlalindendoğan talepleri ileri sürebilir.

Article 85 of the Law on Intellectual and Artistic Works numbered 5846 introduces certain rules for_x000D_ the publication of letters, memoirs and similar writings. The aim of this law article is to protect the_x000D_ information about the intimate and private lives of the author or the addressee. The publication of_x000D_ writings containing such information without a justifying reason causes violation of the personality_x000D_ right. Therefore, in case of violation of the article, the persons whose right of intimate or private life is_x000D_ breached, may claim the remedies arising from the violation of the personality right.
(Protection of Letter, Memoir and Similar Writings Within the Scope of the Personality Right)